(untitled) (Revista Cientifica Ingenio Magno, 2021)
From the different existing methods for plastic recycling, pyrolysis offers the possibility of solving mechanical recycling limitations, which requires large amounts of clean, separate and homogeneous plastic waste in order to be able to guarantee the quality of the final product. In pyrolysis, it is not necessary to classify or clean the different types of plastic waste and it is possible to process waste contaminated with food and chemical products, such as insecticides, herbicides and fertilizers, reducing classification and cleaning costs. Pyrolysis consists of the chemical decomposition of plastic materials by thermal degradation in the absence of oxygen. In this work the results obtained from the pyrolysis of waste expanded polystyrene (EPS) in a batch reactor, varying the pyrolysis temperature are presented. It was experimented with a mass of 500 g and temperatures of 350, 400 and 450 ° C. The results indicate that the highest conversion performance in to liquid hydrocarbon was obtained at a temperature of 450 ° C. The lowest yield of liquid hydrocarbon was obtained at the temperature 350 ° C.